Problems of the conception of self-evaluation - Valickas, G. (Psichologija, 1987)
The present article deals with the problems concerning conceptualization of self-evaluation in Soviet and foreign literature. The article gives a critical view on the present situation. Self- evaluation is analysed by paying due attention to the different forms of its realization on in real life, by distinguishing and discussing the four oppositions: (a) conscious-unconscious, (b) affective-cognitive, (e) general-partial, (d) demonstrative - real. The definition of self-image is given at the end of the article (this concept is preferred). Self-image is a product of reflection of self-information in relation with certain values and standards that realize themselves in the unity of conscious and unconscious, affective and cognitive, general and partial, demonstrative and real forms.